Plate of ribs: single institution's matched comparison of patients managed operatively and non-operatively for rib fractures. Issue 1 (5th November 2020) - Griffard, Jared; Daley, Brian; Campbell, Marc; Martins, Danilo; Beam, Zach; Rowe, Sean; Taylor, Jessica
Abstract : Background: Rib fractures are associated with significant morbidity and mortality in polytraumatized patients. There is considerable variability in the management (operative vs. non-operative) and timing of operative intervention. Although Eastern Association for the Surgery of Trauma (EAST) guidelines recommend early operative intervention in patients with flail chest, there are no strong recommendations regarding operative fixation in patients with a non-flail chest rib fracture pattern. Methods: We reviewed our Trauma Quality Improvement Program database for patients aged 18 to 99 who underwent operative intervention of ribs from January 2016 to July 2019. We examined hospital length of stay (LOS), intensive care unit (ICU) LOS, ventilator days, Injury Severity Score, age, discharge disposition and packed red blood cell transfusions. Similarly, we collected data from patients aged 18 to 99 who had one or more rib fractures in this time frame. We compared results in a 4:1 ratio of patients managed non-operatively to patients managed operatively. The patient groups were matched based on age, number of rib fractures and presence of bilateral rib fractures. Results: Between January 2016 and July 2019, 33 of 4189 total patients diagnosed with rib fractures underwent operative fixation; the matched non-operative group consisted of 132 patients. The statistically significant differences included presence of bilateral rib fractures, displaced rib fractures and flail chest segments. The median ICU days were longer in the operative group (6.0 vs. 3.5 days). A subgroup analysis of patients without flail segments demonstrated a significant presence of displaced rib fractures. Our single-institution matched comparison of outcomes in operative intervention versus Non-operative Management (NOM) of rib fractures found an increased median number of ICU days. Patients who underwent operative intervention often stayed in the ICU preoperatively and postoperatively for aggressive pulmonary hygiene and pain control, suggesting observer bias. The increased incidence of displaced rib fractures and the presence of a flail segment in the operative group demonstrate congruence with EAST guidelines. A subgroup analysis of patients without flail segment did not demonstrate differences in outcomes nor shoulder girdle injury characteristics. Level of evidence: This article presents level III evidence that can be used by other clinicians to analyze eligibility for patients to undergo surgical stabilization of rib fracture (SSRF) and to provide counterarguments for performing SSRF in a heterogenous group of patients.